The Bride of the Nile $1 (BVolume 01s - Ebers, Georg, 1837-1898; Bell, Clara, 1834-1927 (Salt Lake City, UT : Project Gutenberg, 2004)
"The Bride of the Nile $1 (BVolume 01" by Georg Ebers is a historical novel written in the late 19th century. Set in sixth-century Egypt during the Arab conquest, the story explores the complexities of cultural conflict and religious strife through the lives of its key characters, including the merchant Haschim and the governor Mukaukas George. At the start of the novel, the setting of Egypt is introduced, oscillating between decay and the aftermath of the Arab conquest. A caravan arrives in Memphis, drawing attention to the city$1 (Bs decline from its former glory. We meet Haschim, an aged merchant with a kind yet weary demeanor, who interacts with local guides and expresses nostalgia for a more prosperous time. Meanwhile, the narrative hints at the personal tragedies of Mukaukas George, the governor, whose family has suffered due to the changes in power dynamics. The tensions between religion and identity form the backdrop of the story, foreshadowing potential conflicts as we are introduced to Orion, the governor$1 (Bs son, and Paula, a young woman with a noble heritage but complicated circumstances. This opening number provides a rich foundation for exploring themes of love, loyalty, and cultural intersection against a textured historical landscape. (This is an automatically generated summary.)s
Release date is 2004-04-01
This eBook was produced by David Widger
Keywords: German fiction -- Translations into English; Egypt -- History -- Fiction